Perbandingan beberapa ujian kebagusan penyuaian untuk taburan normal dan taburan logistik - Faridatulazna A. Shahabuddin,; Norkhairul Aizura Nordin,; Kamarulzaman Ibrahim,; Abdul Aziz Jemain, (Penerbit Universiti Kebangsaan Malaysia, 2010)

(untitled)
Goodness of fit (GOF) test is a statistical technique that can be used to determine whether or not a data set follows certain statistical distributions. There are various GOF statistics that can be applied such as Kolmogorov Smirnov (KS), Anderson-Darling (AD) and Cramer- von- Mises (CV). In this paper a study is conducted to investigate the performance of several selected goodness of fit tests which include KS, AD, CV, three test statistics of Zhang and a proposed modified GOF test which incorporates a variance stabilising transformation. The performance of these tests is studied for testing normal and logistic distributions for various sample sizes. It is found that Zhang’s test is the most powerful and followed closely by our proposed GOF test